2001
DOI: 10.1097/00005768-200105000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of creatine loading on long-term sprint exercise performance and metabolism

Abstract: The results of this study indicate that Cr ingestion (20 g.day-1 x 5 d) improved exercise performance during 80 min of repeated-sprint exercise, possibly due to an increased TCr store and improved PCr replenishment rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 0 publications
1
30
1
9
Order By: Relevance
“…Previous studies that have showed benefits of short-term (5-6 days) creatine supplementation have used similar performance protocols (e.g., repetitive or long sprints) as those used in this present study. But in contrast to this study, the other researchers used a typical loading phase (20 g·d Ϫ1 ) (4,5,8,17,20,24). The basic premise behind the use of a 5-to 6-day loading phase is to maximize muscle creatine concentrations in a short period of time (12).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies that have showed benefits of short-term (5-6 days) creatine supplementation have used similar performance protocols (e.g., repetitive or long sprints) as those used in this present study. But in contrast to this study, the other researchers used a typical loading phase (20 g·d Ϫ1 ) (4,5,8,17,20,24). The basic premise behind the use of a 5-to 6-day loading phase is to maximize muscle creatine concentrations in a short period of time (12).…”
Section: Discussionmentioning
confidence: 98%
“…) as their supplement regime (4,5,17,20,24). There is only one investigation known that has shown there to be ergogenic benefits of a low-dose creatine supplementation (3).…”
mentioning
confidence: 99%
“…kg -1 ). Reen et al (23) verificaram Gráfico 1. Potência pico antes (PRÉ) e depois (PÓS) de sete dias de treinamento com e sem suplementação de creatina.…”
Section: Discussionunclassified
“…Durante uma atividade física de alta intensidade, o ADP (difosfato de adenosina) é refosforilado para ATP, utilizando os depó-sitos de fosfato de creatina. A suplementação com creatina pode aumentar tais depósitos em 6-8 vezes, aumentando a disponibilidade de fosfato de creatina para a regeneração do ATP 3,34,35 . Para Nissen & Sharp 23 , existem três mecanismos de ação da creatina na fisiologia do esporte: aumento na força muscular, como resultado do aumento da expressão de miosina de cadeia pesada; ação anticatabólica; e aumento do volume celular, estimulando a síntese proteica.…”
Section: Creatinaunclassified